NMDA Antagonists for Refractory Seizures - Zeiler, F. A.; Teitelbaum, J.; Gillman, L. M.; West, M. (Neurocritical care, 2014)
Refractory status epilepticus (RSE) poses significant challenge, with a variety of novel therapeutics employed. Our goal was to evaluate the effectiveness of N -methyl d -aspartate (NMDA) receptor antagonists in the control of RSE. We performed a systematic review of all the literature, with all articles pulled from MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to September 2013), reference lists of relevant articles, and gray literature. Two reviewers independently identified all manuscripts pertaining to the administration of NMDA receptor antagonists in humans for the purpose of controlling refractory seizures. Secondary outcome of adverse NMDA antagonist effects and patient outcome was assessed. Two reviewers independently extracted data including population characteristics, treatment characteristics, and outcomes. The strength of evidence was adjudicated using both the Oxford and GRADE methodology. Our search strategy produced a total of 759 citations. Twenty-three articles, 16 manuscripts, and seven meeting proceedings, were considered for the review with all utilizing ketamine for seizure control. Only three studies were prospective studies. Fifteen and nine studies pertained to adults and pediatrics, respectively. Across all studies, of the 110 adult patients described, ketamine was attributed to electroencephalogram seizure response in 56.5 %, with a 63.5 % response in the 52 pediatric patients described. Adverse events related to ketamine were rare. Outcomes were poorly documented in the majority of the studies. There currently exists Oxford level 4, GRADE C evidence to support the use of ketamine for refractory seizures in the adult and pediatric populations. Further prospective study of early ketamine administration is warranted.